Analisis Manajemen Risiko Operasional Pada Usaha Penyewaan Motor PT VRM Trans - Ifli Fateah (AKSIOMA : Jurnal Manajemen, 2026)
This study aims to analyze operational risk management in PT VRM Trans’ motorcycle rental business in Bali using the ISO 31000 framework. A descriptive qualitative approach was employed, with data collected through semi-structured interviews with the business owner, operational administrator, and field officers, as well as direct observation of booking, vehicle handover, and return processes. Data analysis followed the ISO 31000 stages: risk identification, analysis, evaluation, and treatment. The main operational risks include vehicle damage, accidents, late returns, communication issues with renters, and vehicle theft, with vehicle damage and theft posing the greatest threat to business sustainability. These findings are expected to serve as a reference for similar vehicle rental businesses in improving operational risk management.